Excess risk of hip fractures attributable to the use of antidepressants in five European countries and the USA - Prieto-Alhambra, D; Petri, H; Goldenberg, J; Khong, T; Klungel, O; Robinson, N; De Vries, F (2014)
The association between antidepressant use and hip fracture remains unclear. We conducted a systematic review to estimate Population Attributable Risks (PAR) for France, Germany, Italy, Spain, UK, and the USA. We report a heterogeneous prevalence of antidepressant use and related PARs, both lowest for Italy and highest for the USA. Introduction: Antidepressant use has been associated with an increased hip fracture risk in observational studies. However, the potential contribution of antidepressant consumption on the population rate of hip fractures has not been described. Our aim was to estimate the impact of the use of different classes of antidepressants on the rate of hip fracture at a population-level in France, Germany, Italy, Spain, the UK, and the USA. Methods: We conducted a systematic literature review to estimate the pooled relative risk (RR) of hip fracture according to use of antidepressants. Prevalence rates of antidepressant use (Pe) in 2009 were calculated for each country using the The Intercontinental Medical Statistics database and three public databases from Denmark, the Netherlands, and Norway. Both the RR and Pe were used to calculate PAR of hip fractures associated with antidepressant use. Results: The literature review showed an increased risk of hip fractures in antidepressant users (RR, 1.7; 95 % confidence interval (CI), 1.5-2.0). Rates of antidepressant use showed considerable differences between countries, ranging from 4.4 % (Italy) to 11.2 % (USA) in the year 2009. The estimated PAR of antidepressants on hip fracture rates were 3.0 % (95 % CI, 2.0-4.1; Italy), 3.1 % (95 % CI, 2.1-4.3; Germany), 3.8 % (95 % CI, 2.6-5.3; France), 4.8 % (95 % CI, 3.3-6.5; Spain), 4.9 % (95 % CI, 3.4-6.8; UK), and 7.2 % (95 % CI, 5.0-9.9; USA). PARs differed for different types of antidepressants, with highest attributable risks for selective serotonin reuptake inhibitors. Conclusions: These findings suggest that the potential contribution of antidepressant use to the population rate of hip fractures in the five large EU countries and the USA varies between 3 and 7 %. © 2014 International Osteoporosis Foundation and National Osteoporosis Foundation.